MARKETING STRATEGIES IN IMPROVING THE COMPETITIVENESS OF MICRO, SMALL AND MEDIUM ENTERPRISES (MSMEs) FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Henry, Henry Martin Adriansyah; Fitri (EL-EMIR Institute, 2026)
This study aims to determine the marketing strategies implemented by the Pirlisae Lidi Craft MSME and how these strategies are viewed from an Islamic economic perspective. The study used a qualitative approach with a case study method. Data were obtained through in-depth interviews, direct observation, and documentation at the business location. The results indicate that the implemented marketing strategies include developing environmentally friendly waste-based ethnic products, setting fair prices, promoting through education and social media, and distributing through local events and networking. This strategy reflects Islamic economic principles such as shiddiq (honesty), amanah (trustworthiness), fathanah (intelligence), tabligh (communicativeness), and syaja'ah (courageousness). Furthermore, the Pirlisae Lidi MSME has strategic advantages over its competitors, such as partnerships with large companies, involvement in business incubation programs, and market education through craft training. This strategy has a direct impact on increasing competitiveness, as evidenced by annual revenues reaching IDR 150 million.